2019
DOI: 10.14814/phy2.14313
|View full text |Cite
|
Sign up to set email alerts
|

Rapid gut microbiome changes in a world‐class ultramarathon runner

Abstract: In 2007 the National Institutes of Health launched the Human Microbiome Project (HMP), an interdisciplinary research initiative seeking to characterize the contribution of human gut microbiota to health and disease (Turnbaugh et al., 2007). Subsequent findings have demonstrated compelling relationships between human gut microbiome composition and many leading causes of death worldwide including cardiovascular disease (Wang et al., 2011), diabetes (Larsen et al., 2010), and cancer (Ahn et al., 2013). Although t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 26 publications
1
63
2
Order By: Relevance
“…Specifically, Keohane et al reported that the Shannon index of gut microbiota increased for four male athletes, with an average age 26.5 years, upon completing a 4998.55-kilometer east-west transatlantic rowing race [28]. Grosicki et al found that the Shannon index of gut microbiota increased for a world-class ultramarathon runner with aged 32 years after completing the 163 km mountain race [29]. One study showed that alpha diversity of gut microbiota for 13 swimmers had a significant increase in Shannon index and inverse Simpson index after daily swimming training for 6 weeks [30].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Keohane et al reported that the Shannon index of gut microbiota increased for four male athletes, with an average age 26.5 years, upon completing a 4998.55-kilometer east-west transatlantic rowing race [28]. Grosicki et al found that the Shannon index of gut microbiota increased for a world-class ultramarathon runner with aged 32 years after completing the 163 km mountain race [29]. One study showed that alpha diversity of gut microbiota for 13 swimmers had a significant increase in Shannon index and inverse Simpson index after daily swimming training for 6 weeks [30].…”
Section: Discussionmentioning
confidence: 99%
“…These findings may be in part due to beneficial effects of exercise on the gut biome [ 167 , 168 ]. Gut biome changes are typically associated with improvements in microbiota diversity, inflammatory markers, metabolic profiles, and immune responses [ 167 169 ].…”
Section: Long-term Health Implications: Key Aspects By Organ Systemmentioning
confidence: 99%
“…To date, the majority of research on this topic has sought to characterize the effects of aerobic exercise on the microbiome [ 171 , 172 , 173 , 174 ]. Among these studies, three notable alterations in the gut microbiome have been consistently observed: (1) Increased biodiversity, (2) Greater production of SCFA’s, such as butyrate, and (3) Enhanced gut motility [ 171 , 172 , 173 , 174 , 175 ].…”
Section: Lifestyle Factors Contributing To Age-related Microbiome mentioning
confidence: 99%